2020
DOI: 10.14529/hsm200216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Sports-Specific Approach in Physical Education of Secondary School Students With Health-Related Issues

Abstract: Aim. The article deals with the evaluation of experimental methods in the physical education of students with different nosologies based on a sports-specific approach. Materials and methods. The study involved 90 secondary school students (grades 5–6) with health-related issues. In the experimental group (EG, n = 45), training sessions were conducted according to the deve­loped program that included volleyball and Russian lapta elements. In the control group (CG, n = 45), students were engaged in traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In secondary education, the impact of sports practice on physical development, adaptation skills, physical fitness, and functional status has also been evaluated. It was observed that the functional capacity of the body is associated with the development of skills, strength and coordination, creating a healthier lifestyle for people (Parfenova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In secondary education, the impact of sports practice on physical development, adaptation skills, physical fitness, and functional status has also been evaluated. It was observed that the functional capacity of the body is associated with the development of skills, strength and coordination, creating a healthier lifestyle for people (Parfenova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%